Advances in Manufacturing II Volume 4 - Mechanical Engineering - Gapiński, Bartosz; Szostak, Marek; Ivanov, Vitalii; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers a variety of topics related to machine manufacturing and concerning machine design, product assembly, technological aspects of production, mechatronics and production maintenance. Based on papers presented at the 6th International Scientific-Technical Conference MANUFACTURING 2019, held in Poznan, Poland on May 19-22, 2019, the different chapters reports on cutting-edge issues in constructing machine parts, mechatronic solutions and modern drives. They include new ideas and technologies for machine cutting and precise processing. Chipless technologies, such as founding, plastic forming, non-metal construction materials and composites, and additive techniques alike, are also analyzed and thoroughly discussed. All in all, the book reports on significant scientific contributions in modern manufacturing, offering a timely guide for researchers and professionals developing and/or using mechanical engineering technologies that have become indispensable for modern manufacturing. .
Requirements Engineering for Production Transfer to Developing Countries -- Structural Indicators for Business Process Redesign Efficiency Assessment -- Examination of the Mediating Effects of Physical Asset Management on the Relationship Between Sustainability and Operational Performance -- Assessment of the Small Enterprise's Maturity to Improvement Projects Based on the Lean Six Sigma Concept -- Technical Culture Maturity as a Manifestation of Implementation of Lean Management Principles - Situation in Agricultural Machinery Sector -- The Analysis of the Occurrence of Faults in Passenger Cars as an Element of Improving the Management of the Production Process.
Keywords: Engineering design; Manufactures; Ceramic materials; Engineering Design; Machines, Tools, Processes; Ceramics